Elaboración de objetos de aprendizaje sobre cuentos, leyendas y rimas de Loja, para la asignatura de lengua y literatura del quinto grado de educación general básica de la escuela ciudad de Loja, período 2016 – 2017. - Jara Elizalde, Talia Rosario (2018)
The present investigation was carried out in the province of Loja, canton of Loja in the parish of the Valle; with the objective of developing learning objects as didactic support to improve the teaching-learning process in the language and literature subject of the fifth year of Basic General Education at the School "Ciudad de Loja" from the Loja city, 2016 – 2017 academic year, for this reason, it contains the process of elaboration of learning objects for the first three units of the Language and Literature subject of the fifth year EGB at the school of Basic Education "Ciudad de Loja", these objects present the possibility to do the classes more enjoyable, interactive and dynamic in order to strengthen the knowledge shared at the beginning of the class. The process of elaboration of the different learning objects was carried out with the help of the AODDEI methodology, which, due to its structure, it allows the development of these objects in an organized and adequate way, achieving some pedagogical and didactic objectives. Some tools used were Exelearnig, Adobe Illustrator, Builder and others, which allowed to reach the final product. Based on this methodology, three learning objects were developed for the Language and Literature subject. These objects contain activities, images, videos and evaluations. The objects were validated by teachers and students, to finish, a cognitive test was applied to verified the achievement of the learning objectives. 5 Finally, the present work has been placed in the repository of the Informática Educativa career at the Universidad Nacional de Loja, allowing it to be accessible to the general public.